2000
DOI: 10.1117/12.384498
|View full text |Cite
|
Sign up to set email alerts
|

Dose-efficient system for digital mammography

Abstract: We are developing a dose-efficient system for digital mammography. The system incorporates a refractive x-ray lens combined with a photon counting silicon sensor system. The system matches the digital nature of x-rays and maximum information can be extracted from the transmitted x-ray beam. The photon counting sensor system opens the possibility to weight each photon according to its information content. High-energy photons with little contrast information can be weighted low while low energy photons are weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The imaging system is said to be "quantum limited" [29,30]. With a pixel size of 50 µm (10 lp/mm), Sectra asserts that good quality imaging is obtained for 1/5 of the usual doses [34,35].…”
Section: Scanning Systemsmentioning
confidence: 99%
“…The imaging system is said to be "quantum limited" [29,30]. With a pixel size of 50 µm (10 lp/mm), Sectra asserts that good quality imaging is obtained for 1/5 of the usual doses [34,35].…”
Section: Scanning Systemsmentioning
confidence: 99%
“…Due to the recent advances in chip level multichannel detector electronics, faster and more powerful computers, and new detector technologies, photon counting x-ray imaging detectors have come closer to their practical realization. 16,32,33 In the present study, a photon counting detector based on MCP was developed and evaluated for x-ray imaging. The system has shown that the spatial resolution and noise are acceptable for medical x-ray imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, the count rate requirement can be satisfied using multichannel ASIC readout electronics, 32,33 where an independent amplifier-counter chain reads out each of the anode strips. This electronics has recently been developed for x-ray detectors based on semiconductors such as a-Si 16 and CdZnTl. 34 Currently, the pulse shaping time of the ASIC electronics can be as short as 50-100 ns, and count rate can reach up to 2 MHz/channel, with approximately 10% dead time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photon-counting X-ray detectors applied to mammography and radiography have shown a dose reduction of 40% to 400% while maintaining sufficient contrast for these applications [4], [5]. Simulations have shown that photon-counting along with optimal energy weighting can increase dose efficiency up to 40% for digital mammography as compared to a conventional integrating system [6]. One group has reported that the lesion detection signal to noise ratio is significantly affected by the energy dependence of the detector’s quantum efficiency and the varying contrast carried by different energies in the beam spectrum [4].…”
Section: Introductionmentioning
confidence: 99%